Bird of Minerva Havoc in Hiaasen's Hoot - Ramadhan, Muhammad Royhan; Agustina, Mia Fitria; Trisnawati, Ririn Kurnia (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2024)
PurposeThis research aimed to study the connection and its consequences of massive development, particularly on the urban areas, towards burrowing owl's population decline and its effect. MethodThe qualitative method was applied to assist the data analysis process in this research. The data are taken from narrative and dialogue within the story. Ecocriticism theory is also implemented to help analyze the effect of urbanization in the story. Results/findingsThe research found that urbanization has dreadful consequences on environment. Urbanization not only drives burrowing owl's decline in population, it also disrupts the food chain system, and affects the population of pest. ConclusionThe study concluded that the effects of urbanization have a broader impact for the environment. Its negative impact can cause mayhem for human life. In accordance with that, this research suggests that urbanization must be planned carefully and consider the effect for the nature and ecosystem.